Pemenuhan Peraturan Pelabelan pada Produk IRTP di Kabupaten Kebumen - Joko Hermanianto; Audia Ari Purwandani; Tjahja Muhandri (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2021)
Label regulations on food products must be adhered by food industries, including SMEs. The lack of awareness or understanding of SMEs on food labeling regulation causes non-complience of SMEe food products with regulations. The objective of this study was to evaluate the level of compliance with labeling regulations and consumer awareness of the labels on SMEs food products in Kebumen. Purposive sampling was used to determine the sample size. The data from product labels was analyzed by content analysis techniques on four distinct groups of elements, i.e. technical labeling, label writing, minimal information, and information that cannot be included. SMEs products that met writing labeling requirement were 27% and those that fulfilled the minimum label information requirement (excluding halal provision) were 40.81%. The food product with halal label was only 18%.